Analisis Pengelolaan Keuangan pada Pelaku UMKM di Pasar Beringharjo Yogyakarta untuk Meningkatkan Kinerja Usaha dan Keberlanjutan Bisnis - Muhammad Ramadhan Mokodompit; Nugraeni Nugraeni (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to provide an in-depth analysis of financial management practices among Micro, Small, and Medium Enterprises (MSMEs) operating in Beringharjo Market, Yogyakarta, focusing on four key indicators: financial planning, recording, reporting, and internal control. A descriptive qualitative approach was employed, with data collected through semi-structured interviews, participatory observation, and documentation from selected MSME owners. The findings reveal that all respondents acknowledge the importance of bookkeeping in business sustainability; however, a significant proportion have not adopted systematic methods for recording debts, receivables, and inventory. Although all respondents prepare profit and loss statements, only around half utilize these reports as a reference for strategic decision-making. Internal control is identified as the most underdeveloped aspect, marked by the absence of cash reconciliation procedures, inventory verification, and basic internal audits. This lack of structured control mechanisms heightens the risk of financial discrepancies and operational inefficiencies. Moreover, limited financial literacy and the absence of formal accounting training further contribute to inconsistent application of sound financial practices. Based on these observations, the study recommends the implementation of targeted capacity-building programs that include practical, hands-on training in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). These initiatives should be accompanied by continuous mentoring from local government agencies and market management to ensure long-term sustainability. Strengthening financial literacy, enhancing systematic management processes, and embedding effective internal controls are critical steps to improving accountability, informed decision-making, and overall business resilience for MSMEs in traditional markets. This research offers valuable insights into the unique financial management challenges faced by small-scale traders and provides practical solutions for improving their economic performance and competitiveness.